Evaluation of Combination of Microneedling with Tacrolimus in the Treatment of Stable Vitiligo - Saurabh Sharma; Parwaaz Matharoo; Roopam Bassi (Sociedade Portuguesa de Dermatologia e Venereologia, 2021)
Introduction: Vitiligo is an amelanotic disorder that can manifest as localized patches to near total body depigmentation. It is considered a cosmetic disease but it is accompanied by extensive psychological effects. Multiple treatments have been tried until now but no single method has achieved the desired response. Tacrolimus is frequently used for vitiligo treatment with few adverse effects. Microneedling is a newer modality of therapeutic wounding that augments drug absorption. Combination of microneedling and tacrolimus have been tried to improve the repigmentation response in vitiligo. Our objective was to assess the safety and efficacy of this combined modality. Methods: Forty patients were subjected to combination of tacrolimus 0.1% ointment and microneedling at 2 week intervals for maximum 10 sessions with a follow-up period of 6 months. Assessment was based on grading of repigmentation and clinical improvement according to vitiligo noticeability scale. Results: Excellent repigmentation was observed in 30% cases. Improvement was significantly higher in lesions present on the head and neck. Mucosal vitiligo also showed good to excellent response. No severe side effects were reported. No complications or recurrences were observed during the follow-up period. Conclusion: Combination of microneedling and tacrolimus was found to be safe and efficacious in the treatment of stable vitiligo.